Discovery of Small Molecule KCC2 Potentiators Which Attenuate In Vitro Seizure-Like Activity in Cultured Neurons - Prael III, Francis J.; Kim, Kwangho; Du, Yu; Spitznagel, Brittany D.; Sulikowski, Gary A.; Delpire, Eric; Weaver, C. David (Frontiers in Cell and Developmental Biology, 2022)
KCC2 is a K+-Cl− cotransporter that is expressed in neurons throughout the central nervous system. Deficits in KCC2 activity have been implicated in a variety of neurological disorders, including epilepsy, chronic pain, autism spectrum disorders, and Rett syndrome. Therefore, it has been hypothesized that pharmacological potentiation of KCC2 activity could provide a treatment for these disorders. To evaluate the therapeutic potential of pharmacological KCC2 potentiation, drug-like, selective KCC2 potentiators are required. Unfortunately, the lack of such tools has greatly hampered the investigation of the KCC2 potentiation hypothesis. Herein, we describe the discovery and characterization of a new class of small-molecule KCC2 potentiator. This newly discovered class exhibits KCC2-dependent activity and a unique mechanistic profile relative to previously reported small molecules. Furthermore, we demonstrate that KCC2 potentiation by this new class of KCC2 potentiator attenuates seizure-like activity in neuronal-glial co-cultures. Together, our results provide evidence that pharmacological KCC2 potentiation, by itself, is sufficient to attenuate neuronal excitability in an in vitro model that is sensitive to anti-epileptic drugs. Our findings and chemical tools are important for evaluating the promise of KCC2 as a therapeutic target and could lay a foundation for the development of KCC2-directed therapeutics for multiple neurological disorders.